2019
DOI: 10.1016/j.psychres.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Measuring facets of reward sensitivity, inhibition, and impulse control in individuals with problematic Internet use

Abstract: INTRODUCTION: Problematic Internet Use (PIU) is the inability to control the amount of time spent on the Internet. Research indicates that abnormalities in reward sensitivity, sensitivity to punishment, and impulse control drive addictive behaviors such as substance abuse and gambling disorders, but it is unclear whether this is also the case in PIU. METHODS: Behavioral tasks and scales were completed by 62 participants (32 PIU individuals and 30 no-PIU individuals) to assess reward sensitivity, sensitivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 71 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…Internet addiction disorder (IAD) is considered as an inability of individuals to control their internet use, resulting in marked distress and functional impairment in daily life such as psychological, social, academic, and professional problems (1). The overall prevalence of IAD ranges from 1.5 to 8.2% in the United States and Europe (2).…”
Section: Introductionmentioning
confidence: 99%
“…Internet addiction disorder (IAD) is considered as an inability of individuals to control their internet use, resulting in marked distress and functional impairment in daily life such as psychological, social, academic, and professional problems (1). The overall prevalence of IAD ranges from 1.5 to 8.2% in the United States and Europe (2).…”
Section: Introductionmentioning
confidence: 99%
“…Functional alterations in the reward network are associated with addiction, depression, and OCD (Park et al, 2019 ). Similarly to behavioral addictions, it has been shown that both IUD and IGD are related to abnormalities in reward processing, inhibition, and impulse control (e.g., Brand et al, 2016 ), with increased reward sensitivity and sensitivity to punishment in individuals with IUD (Vargas et al, 2019 ). These speculations seem to be supported by the findings we obtained when exploring the possible patterns of relationships among impulsive-compulsive domain, affective domain , and substance abuse variables in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive investment may reflect compulsive tendencies in managing the relational self. ‘ Hunting ’ processes (i.e., reward-seeking) comprised active manipulation for higher reward acquisition, triggered primarily by the variable reward reinforcement similar to gaming, acting as potential antecedent to problematic use due to reinforcement sensitivity [6,89] and neurobiological activation in neural regions implicated in reward processing, social cognition, imitation, and attention [90]. However, behavioral reinforcement factors have not been sufficiently studied to date [91], particularly in relation to their interaction with individual and other situational factors.…”
Section: Discussion Of the Emergent Modelmentioning
confidence: 99%